Ultrafine CuO/graphene oxide cellulose nanocomposites with complementary framework for polycyclic aromatic hydrocarbon pollutants removal - Cao, Mengbo; Zhang, Hanmin; Wei, Xingyue; Tian, Yu (Water research (Oxford), 2024)
•Ultrafine CuO/Graphene Oxide Cellulose Nanocomposites was synthesized for contaminant removal.•The integrated-sorption and designed well-active adsorbent break the upper boundary limited in adsorption process.•The excellent selectivity (nearly 100 %) of tetracycline is performed out.•Enriched antibiotics on materials facilitate the pollutant mineralization and adsorbent cycle in regeneration process. Efficient and sustainable methods for eliminating polycyclic aromatic hydrocarbon pollutants (PAHPs) are in highly desired. Proven technologies involve physical and chemical reactions that absorb PAHPs, however they encounter formidable challenges. Here, a bottom-up refining-grain strategy is proposed to rationally design ultrafine CuO/graphene oxide-cellulose nanocomposites (LCelCCu) with a mirror-like for tetracycline (TC) to substantially improve the efficient of the purification process by active integrated-sorption. The LCelCCu captures TC with a higher affinity and lower energy demand, as determined by sorption kinetic, isotherms, thermodynamics, and infrared and X-ray Photoelectron Spectroscopy. The resulting material could achieve ultra-high sorption capacity (2775.23 mg/g), kinetic (1.2499 L g−1 h−1) and high selectivity (up to 99.9 %) for TC, nearly surpassing all recent adsorbents. This study simultaneously unveils the pioneering role of simultaneous multi-site match sorption and subsequent advanced oxidation synergistically, fundamentally enhancing understanding of the structure-activity-selectivity relationship and inspires more sustainable water purification applications and broader material design considerations. [Display omitted]